Equilibrium pricing sequence in a co-opetitive supply chain with the ODM as a downstream rival of its OEM. (December 2015) - Niu, Baozhuang; Wang, Yulan; Guo, Pengfei
Abstract: We study three basic price competition games engaged in by an original equipment manufacturer (OEM) and its competitive original design manufacturer (ODM): a simultaneous pricing game, an OEM-pricing-early game, and an ODM-pricing-early game. The ODM provides contract manufacturing service to the OEM and competes with this OEM in the consumer market by selling self-branded products. We consider two market environments: the ODM market and the OEM market. For the ODM market, we show that a sequential pricing game arises as the outcome preferred by the OEM and its ODM. Moreover, the equilibrium that the OEM prices early risk-dominates the one that the ODM prices early. Nevertheless, for the OEM market, the simultaneous pricing game and the sequential pricing game can both arise and be sustained. We also demonstrate that it is in their mutual interest to be friends rather than foes. Abstract : Highlights: We study the price competition between an OEM and its competitive ODM. We apply the endogenous timing game to investigate their price leadership preference. We consider two market environments: the OEM market and the ODM market. We show that it is in their mutual interest to choose to be friends instead of foes. We also discuss the impact of price negotiation and capacity limitation.